The Role of Competency on The Effect of Training and Development System toward Job Productivity in The Human Resource Management Universal Corporation (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2020)
Employee development related to job productivity was very necessary in a company organization, because the existence of the program could helped to improving employee competency. The importance of education and training based on competency would enhanced the ability and build character of the human resources concerned. Referring to this, Human   Resource Management Universal Corporation were established company in 2009 and engaged in consulting services related to training and human resource development and had 64 trainers of national and international certified and was trained in providing training and consulting to client. This study aimed to analyzing the effect of training and development system toward productivity jobs through competency on trainers in the Human Resource Management Universal Corporation. The type of this study was an explanatory survey type with used the path analysis method. Based on the results of the study it can be concluded several things, including:  1.)  The  effect  of  training  and  development  system  toward  competency  was significant with value of 0,503; 2.) The effect of training and development system toward job productivity was significant with value of 0,426; 3.) The effect of competency toward job productivity was significant with value of 0,495; 4.) The effect of training and development system toward job productivity through competency was significant with value of 0,248.